1977
DOI: 10.2183/pjab1945.53.95
|View full text |Cite
|
Sign up to set email alerts
|

Comutagenic Action of Norharman and Harman

Abstract: No. 2] Proc. Japan Acad., 53 (1977) 95 26. Comutagenic Action o f Norharman and Harman

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 5 publications
(1 reference statement)
2
24
0
Order By: Relevance
“…Consistent with previous reports (19,30), compounds I.and 2 were found to be potent mutagens ( Table 1). The mutagenic activity obtained with strain TM677 was much greater than the activities associated with compounds such as benzo[a Ipyrene or 2-acetamidofluorene and was comparable to the activity of aflatoxin B1.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous reports (19,30), compounds I.and 2 were found to be potent mutagens ( Table 1). The mutagenic activity obtained with strain TM677 was much greater than the activities associated with compounds such as benzo[a Ipyrene or 2-acetamidofluorene and was comparable to the activity of aflatoxin B1.…”
Section: Resultssupporting
confidence: 92%
“…The intense mutagenicity and cytotoxicity of certain 3-amino-l-methyl-5H-pyrido [4,3-b]indoles in bacterial and mammalian (33) assays and the implications of their possible occurrence as dietary constituents (19,30) prompted us to investigate the mechanism(s) by which they exert their mutagenic effects. Although the compounds of interest bear an obvious structural relationship to those in the 2-aminofluorene series, the much greater mutagenic activity of the indole derivatives suggested that the mechanism(s) by which they are activated metabolically and react with DNA might not parallel the pathways utilized by the aminofluorenes.…”
Section: Discussionmentioning
confidence: 99%
“…1(f), and serves to underline the variability in in vitro test response to be expected with changes in the S-9 mix or overall in vitro metabolism (Ashby and Styles 1 978a, b). These effects closely parallel those produced by norharman with DAB in the Ames assay (Nagao et al, 1977) and those produced by 4'ethylation of DAB, to be discussed later. These observations may also cast some light on the fact that most derivatives of DAB carrying a substituent ortho to the azo bridge are non-carcinogenic (reviewed by Arcos and Argus, 1974).…”
Section: Discussionsupporting
confidence: 57%
“…Whilst DAB can produce a positive effect in the Ames assay, this response cannot be relied upon (Ames et al, 1973;McCann et al, 1975;Purchase et al, 1978;Ashby and Purchase, 1977;Nagao et al, 1977). Such uncertainty is important in a study such as the present one.…”
mentioning
confidence: 83%
“…Their mutagenicities in the Salmonella test system were greatly increased by norharman and harman, which were also found in tryptophan pyrolysate (2). Because norharman and harman themselves have no mutagenic activity, they were called "comutagens."…”
mentioning
confidence: 99%